Elit badmintoncularin smaç vurusu isabet oranlari ve siçrama performanslari iliskisinin degerlendirilmesi - Orhan, Ö.; Çetin, E.; Yarim, I.; Gültekin, O. (International Journal of Human Sciences, 2019)
The aim of this study was to evaluate the relationship between the strength and jump parameters of elite level badminton players in the range oscoref 5, 10, and 15 intervals of smash. A total of 10 male national badminton players with a mean age of 15.2 ± 0.18 years, length of 170.5 ± 2.13 cm, body weight of 59.5 ± 2.48 kg and sports age of 5 ± 1.36 years participated in the study. Leg strength test dynamometer (Prosport-TMR HBD 1000 dynamometer), jump parameters of the subjects were measured with Opto Jump (Microgate, Bolzano). The smash swere performed as 3x30 sec and 3 minutes passive rest protocol was applied after each series. In every 30 seconds, the shots were made by the national team coach with the multishuttle method as 5-10-15. The hit of the parallel smash scored was recorded by the referee. Data analysis was performed using SPSS 23.0 package program. For the relationship between the parameters, Spearman Correlation test and Friedman test were used for comparison of parameters with intermittent jump. As a result of the study, it was seen that there were statistically significant differences in the power and contact time parameters applied during the jumps as the number of smash increased within 30 seconds. In addition, it was found that as the frequency of scored increased, the rate of accuracy and heart rate (KAS) increased. This can be interpreted as a decrease in the scored of the players due to fatigue as the smash frequency increases.